Antimicrobial Activity Of Plant Extracts And Isolation And Characterization Of Alkaloids From Samanea Saman (Jacq.) Merr. Leaves - Sahib Ajam, Sundis Mahdi (2011)
Due to the harmful effects on the occupants and environment, residual toxicity, and carcinogenic nature of synthetic biocides, plant-based biocides may offer safer alternatives for controlling bacterial and fungal bioaerosols that cause sick building syndromes and building deterioration. Therefore, the purpose of this study was to screen local flora for antimicrobial activity against bacteria and fungi isolated from sick enclosed buildings, fractionate and identify the compounds with the highest antimicrobial activities from the methanolic (80% MeOH) extract of Samanea saman leaves.